(3GdOQQ GdfLajI ef GdedJbWGJ GdjhSajIs - (3GdOQGRj GdHMQGfj, GHf YUahQ, jhSa Hf CMeO Hf EHQGgjes ((3UaQ Ydj Hf ESeGYjd GdfLa BHGOjs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj gOi CHUGQ HUGFQfG HCfhGQ GdhdGjI GdMjOQjI (B... (3Qhi GdeTGjN GdKdGKI YWQ Gddg eQGbOge HCSGfjOge Yf GdUGObs
(3BNQgG (B:s
(3BNQgG(B: (3bjd(B: (3hGdeYfi, MUd eG MUd ef JVjb GdOfjG Ydi GdeDefjf hGdTjYI GdeNdUjf hGdJhSYI Ydi GdcGaQjf hGdXGdejf djeMU Gddg GdPjf BefhG hjeMb GdcGaQjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B8: 215s
(3EjVGM Gdecfhf L (B1: 470s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis